Resiko Jatuh pada Klien Stroke yang Menggunakan Kursi Roda di Kabupaten Pamekasan - Abdan Syakura; Aghniya Nisa’asy Shobiri NHJ; Anggeria Oktavisa Denta (Wiraraja Medika : Jurnal Kesehatan, 2021)
Introduction: people who suffer from stroke and immobilization use wheelchair to help move/carry out daily activities on average, so they may be at risk of falling during its usage. This research aimed to comprehend the fall risk assessment in stroke clients with wheelchair at RSUD Dr. H. Slamet Martodirdjo Pamekasan. Methods: This research used a cross sectional descriptive design. Population in this research was 31 stroke clients using wheelchairs in Pamekasan District with the sampling technique using total sampling. This research was conducted in the region of Pamekasan on February, 2021. Data was collected by distributing a Close ended-Multiple choice questionnaire with an ordinal scale containing of 12 question items and then processing the data in the form of editing, scoring, tabulating. Results: Most of the total respondents who have been researched indicate a low risk of falling as 14 people (45%). Conclusion: The Families are expected to provide assistance and supervision to stroke client, especially those who have experienced falling.